Older Women's Fears of Violence: The Need for Interventions That Enable Active Ageing - Barnett, K.; Buys, L.; Lovie-Kitchin, J.; Boulton-Lewis, G.; Smith, Dianne; Heffernan, M. (Routledge, 2007)
Women's fear of violence can impact negatively on their active participation in life. An ageing survey conducted with 2,620 Australian respondents aged 50 to 90 years examined aspects of work, learning, social, spiritual and emotional status, health, vision, home, life events, demographics, and asked an open-ended question about what being actively engaged in life meant. Ordinal regression was carried out on two dependent variables: wanting and needing to learn to discourage violence. Analyses found that as women's age increased, those on lower incomes were more likely than others to say they needed to learn how to discourage violence against them. This paper investigates the variables associated with the findings–transport, finances, news media, home safety, and reduced social interactions. Results highlight the importance of understanding women's fear in the context of personal and social issues, and the need to provide learning opportunities to improve safety and social engagement.